Homo Ludens: A new approach to exercise on the international space station - Nilsson,Robin; Tsantoula,Erieta (2002)
The original task for our final thesis was to solve issues that are connected with exercise on the International Space Station, ISS. Those issues are mainly centered on the conflict between scientific and human needs perfect micro gravity conditions versus the needs to physically challenge the human body. Also psychological matters were central to the project exercise for the sake of science versus exercise for recreation. For us it was evident, that the issues called for a completely new approach to exercise. The objective that we set up for our project was to find this new approach, and also to verify the success of it by exploring ideas with sketches and practical experiments. Investigating the problem from a holistic viewpoint, made us discover more profound issues as the project evolved. Those issues are not centered on exercise, but the living situation for the on-board crew and also the link between the crew and common people of the Earth. It was decided that those issues should be taken into consideration since they can benefit from a different outlook on exercise on orbit. In this new outlook the focus has been somewhat expanded, from containing only medicine and physiology to including fun, sport, competition and challenge in the exercise. The project dealt both with the actual exercises as well as the creation of spaces for exercise. The result is a flexible and decentralized system that is based on the use of space and temporary surfaces rather than existing surfaces. Its components operate in a network, creating advantages that characterizes a central place for exercise. The system was derived from considerations about links between time, space and function in the dynamic living sphere of the ISS.
Keywords: Rörelsehinder